GRAIN GROWTH KINETICS OF AUSTENITIC STAINLESS STEEL 316L AND THE RELATIONS BETWEEN GRAIN SIZES AND HARDNESS UNDER ISOTHERMAL CONDITIONS - Moch. Syaiful Anwar; Mayang Gita Pradisti; Septian Adi Candra; Erie Martides; Efendi Mabruri; Eddy Sumarno Siradj (National Research and Innovation Agency (BRIN), 2022)
316L austenitic stainless steel was usually used in the nuclear power plant. This steel has an austenitic phase at room temperature, and it can change grain size after exposed at high temperatures. The purpose is to investigate grain growth behavior and hardness of 316L austenitic stainless steel after cold-rolled and annealing at a temperature of 1100 °C with holding times of 0, 900, 1800, 2700, 3600 s. The result shows that the grain growth of 316L austenitic stainless steel occurs normally. Austenite grain size of 316L increases with increasing holding time, resulting in hardness decreases. Grain growth of 316L austenitic stainless steel resulting from the experiment shows no difference significant with the prediction.